Methods of swindles in the bank sphere: сriminal-legal aspect - Кришевич, Ольга Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The peculiarities of committing crimes related to fraud in bank lending.